ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ULANG PADA SWALAYAN KOPERASI GUYUB RUKUN DI PANARUKAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING - Mufid, Rozin Khairon; Arief, Mohammad Yahya; Syahputra, Hendra (Jurnal Mahasiswa Entrepreneurship (JME), 2024)
In the current era of globalization, of course, there are many developments that are very rapid and increasingly sophisticated, one of which is the development of retail business businesses. The purpose of this study is to analyze the Role of Product Diversity, Service Quality, and Facilities in influencing Consumer Satisfaction and Repurchase Interest in Guyub Rukun Cooperative Supermarket in Panarukan. This research is an explanatory research. The population in this study is the consumers of the Guyub Rukun Cooperative Supermarket in Panarukan. The sampling technique was determined by simple random sampling. Data analysis and hypothesis testing in this study used the Structural-Partial Least Square Equation Model (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, showed that product diversity did not have a significant effect on consumer satisfaction, Service quality did not have a significant effect on consumer satisfaction, Facilities had a significant effect on consumer satisfaction, Product diversity had a significant effect on repurchase interest, Service quality did not have a significant effect on repurchase interest, Facilities do not have a significant effect on repurchase interest, Consumer satisfaction has a significant effect on repurchase interest. The results of the indirect influence hypothesis test showed that the variable of product diversity on repurchase interest through consumer satisfaction had a negative but insignificant effect, The quality of service for repurchase interest through consumer satisfaction has a negative but not significant effect, the facility for repurchase interest through consumer satisfaction has a positive but insignificant effect.